Thermoplastic resin composition
By using polypropylene-styrene-based multi-chain copolymer in polypropylene, the problem that polypropylene is difficult to improve impact strength and recovery while maintaining high fluidity and softness, achieving multiple performance improvements of the material.
Patent Information
- Application Number
- JP2023507808
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-05
- Filing Date
- 2021-08-06
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-08-06
AI Technical Summary
The prior art is difficult to improve the impact strength and recovery power of polypropylene while maintaining high fluidity and softness.
A polypropylene-styrene-based multi-chain resistive copolymer was used to satisfy specific tanδ peak height and width conditions in the temperature range of -80 to 40°C by dynamic mechanical analysis (DMA).
It achieves high fluidity and softness, while improving the impact strength and resilience of the material, suitable for applications requiring soft touch and high resilience.
Smart Images

Figure 0007670419000033 
Figure 0007670419000034 
Figure 0007670419000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0099168 filed on August 7, 2020, and Korean Patent Application No. 10-2021-0103396 filed on August 5, 2021, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a thermoplastic resin composition comprising polypropylene and a polyolefin-polystyrene multiblock copolymer having a structure in which polystyrene chains are attached to both ends of the polyolefin chain. [Background technology]
[0003] Polypropylene, which is widely used as a material for grips in daily necessities and interior and exterior parts for automobiles, has the advantage of excellent rigidity and moldability, but has the disadvantage of poor impact strength. To compensate for this, polypropylene-based resin compositions containing polypropylene (PP) as the main component and impact modifiers and inorganic fillers have been used. Since the emergence of ethylene-α-olefin copolymers synthesized using metallocene catalysts, ethylene-α-olefin copolymers have begun to be used as impact modifiers for polypropylene. Such mixed compositions of polypropylene and ethylene-α-olefin copolymers have the advantages of compensating for the poor impact strength of polypropylene and compensating for the low rigidity of ethylene-α-olefin copolymers.
[0004] However, when ethylene-α-olefin copolymer is mixed with polypropylene, even if a small amount of polypropylene is added, the soft feel and restoring force of the ethylene-α-olefin copolymer are significantly reduced, and even if ethylene-α-olefin copolymer is added to polypropylene to supplement the impact strength, there is still a limit to ensuring impact resistance in various usage environments.
[0005] Therefore, for materials that require a soft feel and high resilience, styrene-based thermoplastic elastomer Styrene-Ethylene-Butylene-Styrene (SEBS) has been used together with polypropylene. However, SEBS is expensive and has the problem of significantly reducing the fluidity of polypropylene, causing flow marks and short shots.
[0006] Therefore, there is still a demand for development of a thermoplastic resin composition which maintains the high flowability of polypropylene and has a soft feel and high restoring force. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent No. 10-1657925 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a thermoplastic resin composition having high flowability and excellent restoring force. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides a thermoplastic resin composition comprising (1) polypropylene and (2) a polyolefin-polystyrene multiblock copolymer which satisfies the following conditions (a) and (b) in a temperature range of −80 to 40° C. in a graph showing the amount of change in loss tangent (tan δ) (y-axis) with temperature (x-axis) obtained by dynamic mechanical analysis (DMA): (a) tan δ peak height is 0.45-0.60; and (b) tan δ peak half-width is 22.5-30.0°C. Effect of the Invention
[0010] The thermoplastic resin composition according to the present invention exhibits high flowability, as well as a soft feel and high restoring force. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows 1H NMR and 13C NMR spectra of a ligand compound used in the preparation of a polyolefin-polystyrene multiblock copolymer contained in a thermoplastic resin composition according to one embodiment of the present invention. [Diagram 2] FIG. 2 shows 1H NMR and 13C NMR spectra of a transition metal compound used in the preparation of a polyolefin-polystyrene multiblock copolymer contained in a thermoplastic resin composition according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will now be described in more detail to aid in understanding the present invention.
[0013] The terms and words used in the description and claims of the present invention should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0014] The term "composition" as used herein includes mixtures of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0015] The term "polymer" as used herein refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the general term polymer encompasses the term homopolymer, which is commonly used to refer to a polymer prepared solely from one type of monomer, and the term interpolymer, as defined below.
[0016] The term "hybrid polymer" as used herein refers to a polymer made by polymerization of at least two different monomers. Thus, the general term hybrid polymer includes copolymers, which are commonly used to refer to polymers made from two different monomers, and polymers made from more than two different monomers.
[0017] The present invention will be described in detail below.
[0018] The thermoplastic resin composition according to the present invention comprises (1) polypropylene and (2) a polyolefin-polystyrene multiblock copolymer which satisfies the following conditions (a) and (b) in a temperature range of -80 to 40°C in a graph showing the change in loss tangent (tan δ) (y-axis) with temperature (x-axis) obtained by dynamic mechanical analysis (DMA): (a) tan δ peak height is 0.45 to 0.60; and (b) The half-width of the tan δ peak is 22.5 to 30.0°C.
[0019] Each component will be described in detail below. (1) Polypropylene In the thermoplastic resin composition according to an embodiment of the present invention, the polypropylene may be, specifically, a polypropylene homopolymer or a copolymer of propylene and an alpha-olefin monomer, and in this case, the copolymer may be an alternating, random, or block copolymer.
[0020] Specifically, the alpha-olefin monomer may be an aliphatic olefin having 2 to 12 carbon atoms or 2 to 8 carbon atoms. More specifically, ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-itecene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene, or 3,4-dimethyl-1-hexene may be used alone or in combination.
[0021] More specifically, the polypropylene may be any one or a mixture of two or more selected from the group consisting of polypropylene copolymers, propylene-alpha-olefin copolymers, and propylene-ethylene-alpha-olefin copolymers, and in this case, the copolymer may be a random or block copolymer.
[0022] The polypropylene has a melt index (MI) of 0.5 g / 10 min to 100 g / 10 min, measured at 230° C. under a load of 2.16 kg, and more specifically, the melt index (MI) may be 1 g / 10 min to 90 g / 10 min. If the melt index of the polypropylene is out of the above range, problems may occur during injection molding of the thermoplastic resin composition.
[0023] Specifically, in the thermoplastic resin composition according to an embodiment of the present invention, the polypropylene may be an impact copolymer having a melt index (MI) of 0.5 g / 10 min to 100 g / 10 min, specifically 1 g / 10 min to 90 g / 10 min, measured at 230° C. under a load of 2.16 kg, more specifically propylene-ethylene impact copolymer, and the impact copolymer may be included in an amount of 20 wt % to 90 wt %, specifically 30 wt % to 70 wt %, more specifically 40 wt % to 60 wt %, based on the total weight of the polypropylene composite. When the impact copolymer having such physical properties is included in the above content range as polypropylene, strength properties, particularly room temperature strength properties, can be improved.
[0024] The impact copolymer can be produced by a conventional polymer production reaction so as to satisfy the above physical property requirements, or can be obtained commercially and used. A specific example is SEETEC (registered trademark) M1600 manufactured by LG Chemical Co., Ltd.
[0025] In addition, in the thermoplastic resin composition according to an embodiment of the present invention, the polypropylene may be one or more random propylene copolymers having a DSC melting point in the range of 120°C to 160°C and a melt flow rate (MFR) in the range of 5g / 10min to 120g / 10min measured at 230°C and a load of 2.16kg according to ASTM-D 1238, and the random propylene copolymer may be included in an amount of 20wt% to 90wt%, specifically 30wt% to 70wt%, more specifically 40wt% to 60wt%, based on the total weight of the polypropylene-based composite material. When the polypropylene having such physical properties is included in the above content range, the mechanical strength of the thermoplastic resin composition, such as hardness, can be improved. The random propylene copolymer may be produced to satisfy the above physical property requirements using a conventional polymer production reaction, or may be commercially available for use. Specific examples include Braskem (registered trademark) PP R7021-50RNA from Braskem America Inc. and Formolene (registered trademark) 7320A from Formosa Plastics Corporation of America.
[0026] (2) Polyolefin-polystyrene multiblock copolymer In the thermoplastic resin composition according to one embodiment of the present invention, the polyolefin-polystyrene multiblock copolymer is characterized in that it satisfies the following conditions (a) and (b) in a temperature range of -80 to 40°C in a graph showing the change in loss tangent (tan δ) (y-axis) versus temperature (x-axis) obtained by dynamic mechanical analysis (DMA): (a) tan δ peak height is 0.45 to 0.60; and (b) The half-width of the tan δ peak is 22.5 to 30.0°C.
[0027] The loss tangent (tan δ) value means the ratio (E″ / E′) of the loss modulus (E”), which indicates the viscosity of a material, to the storage modulus (E’), which indicates the elasticity of the material, and is used as an index for evaluating the viscoelastic properties of a copolymer.
[0028] Regarding the condition (a), when the value of tan δ as a function of temperature is measured for the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition according to one embodiment of the present invention and the measured value is plotted on a graph with temperature on the x-axis and tan δ on the y-axis, the height of the tan δ peak is 0.45 to 0.60 in the temperature range of −80 to 40° C. Specifically, the height of the tan δ peak may be 0.45 or more, 0.47 or more, 0.48 or more, or 0.50 or more, and may be 0.60 or less, 0.58 or less, 0.57 or less, or 0.55 or less.
[0029] The height of the tan δ peak refers to the y value when the tan δ value is maximum in the x-axis range of -80 to -40°C, and in this case, the tan δ peak can be expressed as one peak in the range of -50 to -30°C.
[0030] If the tan δ peak height is too low, the loss modulus relative to the storage modulus is small, which reduces the degree of energy dispersion and may result in low impact strength. If the tan δ peak height is too high, the flexural strength of the copolymer may be reduced.
[0031] Regarding the condition (b), the polyolefin-polystyrene-based multiblock copolymer has the above-mentioned tan δ peak height and a half-width of the tan δ peak of 22.5 to 30.0° C. Specifically, the half-width of the tan δ peak can be 22.5° C. or more, 23.0° C. or more, 24.0° C. or more, 25.0° C. or more, 25.5° C. or more, or 26.0° C. or more, and can be 30.0° C. or less, 29.0° C. or less, or 28.5° C. or less.
[0032] The half-width of the tan δ peak refers to the temperature range T2-T1 between T1 (low temperature) and T2 (high temperature) at which the half-value of the height of the tan δ peak defined in condition (a) is the value of tan δ, and can be used as an index to interpret how the distribution form of the tan δ value is shown according to the change in temperature in the copolymer. The narrower the half-width of the tan δ peak, the faster the transition from the glass phase to the rubber phase can be made, so the narrower the half-width of the tan δ peak, the higher the impact strength and the more effectively it can be used as an impact modifier.
[0033] If the range of the half width of the tan δ peak is too large, the impact strength of the copolymer is reduced, and there may be a problem that the copolymer does not exhibit sufficient effect when used as an impact modifier.
[0034] As described above, the polyolefin-polystyrene copolymer contained in the thermoplastic resin composition according to one embodiment of the present invention simultaneously satisfies the conditions (a) and (b), and thus exhibits excellent impact strength and can be widely used as an impact modifier in various fields.
[0035] The polyolefin-polystyrene multiblock copolymer may further satisfy the following conditions (c) and (d). (c) The value of tan δ is 0.10 to 0.30 at -10 to -30°C; and (d) The value of tan δ is 0.05 to 0.50 at 15 to 30°C.
[0036] The conditions (c) and (d) satisfy the change and distribution of tan δ value with temperature, as in the above conditions (a) and (b), respectively, and quantitatively express the value of tan δ at low and high temperatures, respectively. The larger the loss modulus value, the smaller the storage modulus value, and the larger the tan δ value, the more efficiently the energy transmitted from the impact can be dispersed when an impact is applied to the copolymer, and therefore the greater the impact resistance and the better the usability as an impact modifier.
[0037] Regarding the condition (c), the value of tan δ at -10 to -30°C may be 0.10 to 0.30, specifically 0.10 or more, 0.15 or more, or 0.17 or more, and 0.30 or less, 0.25 or less, or 0.21 or less. In addition, while satisfying the above range of the value of tan δ, the storage modulus E' may be 1 to 200 MPa, and the loss modulus E" may be 1 to 100 MPa.
[0038] Regarding the condition (d), the value of tan δ at 15 to 30° C. may be 0.05 to 0.50, specifically 0.05 or more, 0.06 or more, and 0.50 or less, 0.40 or less, 0.30 or less, 0.20 or less, or 0.10 or less. In addition, while satisfying the above range of tan δ, the value of storage modulus E' may be 0.1 to 50 MPa, and the value of loss modulus E" may be 0.01 to 5 MPa.
[0039] As described above, the copolymer contained in the thermoplastic resin composition according to one embodiment of the present invention satisfies the values of tan δ under the conditions (c) and (d), and thereby exhibits excellent impact strength both at low temperatures of -10 to -30°C and at high temperatures of 15 to 30°C.
[0040] The weight average molecular weight of the polyolefin-polystyrene multiblock copolymer is 40,000 to 300,000 g / mol, specifically, 50,000 g / mol or more, 60,000 g / mol or more, 70,000 g / mol or more, and 250,000 g / mol or less, 220,000 g / mol or less, 210,000 g / mol or less.
[0041] The molecular weight distribution of the polyolefin-polystyrene multiblock copolymer is 1.0 to 3.0, specifically, it may be 1.5 or more, 1.6 or more, and 3.0 or less, 2.5 or less, 2.0 or less, or 1.9 or less.
[0042] The weight average molecular weight and number average molecular weight are polystyrene-equivalent molecular weights analyzed by gel permeation chromatography (GPC), and the molecular weight distribution is calculated from the ratio of (weight average molecular weight) / (number average molecular weight).
[0043] The polyolefin-polystyrene-based multiblock copolymer may be at least one selected from the group consisting of polystyrene-poly(ethylene-co-propylene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-butene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-pentene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-hexene)-polystyrene block copolymer, polystyrene-poly(ethylene-co-1-heptene)-polystyrene block copolymer, and polystyrene-poly(ethylene-co-1-octene)-polystyrene block copolymer.
[0044] Furthermore, the polyolefin block of the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition of the present invention may contain one or more repeating units represented by the following chemical formula a.
[0045] [ka]
[0046] In the above chemical formula a, R1 is hydrogen; an alkyl having 1 to 20 carbon atoms; an alkyl having 1 to 20 carbon atoms substituted with a silyl group; an arylalkyl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms substituted with a silyl group; n can be an integer from 1 to 10,000.
[0047] According to one embodiment of the present invention, R1 may be hydrogen or alkyl having 3 to 20 carbon atoms.
[0048] According to one embodiment of the present invention, R1 may be hydrogen or alkyl having 3 to 12 carbon atoms, specifically, R1 may be hydrogen or alkyl having 4 to 12 carbon atoms.
[0049] Moreover, the n can be an integer from 10 to 10,000, and specifically, an integer from 500 to 7,000.
[0050] On the other hand, in the chemical formulae shown in the present specification, "*" indicates a linking moiety as the terminal portion of a repeating unit.
[0051] When the polyolefin block contains two or more kinds of repeating units represented by the above chemical formula a, the polyolefin block can contain a repeating unit represented by the following chemical formula b.
[0052] [ka]
[0053] In the above chemical formula b, R1' and R1" are each independently hydrogen, an alkyl having 1 to 20 carbon atoms; an alkyl having 1 to 20 carbon atoms substituted with a silyl group; an arylalkyl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms substituted with a silyl group; wherein R1' and R1" are different from each other, 0 <p<1であり、 n' can be an integer from 1 to 10,000.
[0054] According to one embodiment of the present invention, R1' and R1" may each independently represent hydrogen or an alkyl group having 3 to 20 carbon atoms, specifically, R1' and R1" may each independently represent hydrogen or an alkyl group having 3 to 12 carbon atoms, and more specifically, R1' and R1" may each independently represent hydrogen or an alkyl group having 4 to 12 carbon atoms.
[0055] More specifically, n' can be an integer from 10 to 10,000, and more specifically, an integer from 500 to 7,000.
[0056] According to one embodiment of the present invention, in the above chemical formula b, any one of R1' and R1" may be hydrogen, and the remaining one may be a substituent other than hydrogen among the above-mentioned substituents.
[0057] That is, when the polyolefin block contains two or more kinds of repeating units represented by the chemical formula a, a structure in which R1 is hydrogen and a structure in which R1 is an alkyl having 1 to 20 carbon atoms other than hydrogen; an alkyl having 1 to 20 carbon atoms substituted with silyl; an arylalkyl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms substituted with silyl may be randomly linked, specifically, a structure in which R1 is hydrogen and a structure in which R1 is an alkyl having 3 to 20 carbon atoms other than hydrogen may be randomly linked.
[0058] More specifically, the polyolefin block may be formed by randomly linking a structure in which R1 is hydrogen and a structure in which R1 is alkyl having 3 to 12 carbon atoms in the chemical formula a, and even more specifically, the polyolefin block may be formed by randomly linking a structure in which R1 is hydrogen and a structure in which R1 is alkyl having 4 to 12 carbon atoms in the chemical formula a.
[0059] When the polyolefin block contains two or more types of repeating units represented by the chemical formula a, the polyolefin block may contain a structure in which R1 in the chemical formula a is hydrogen and a structure in which R1 has a substituent other than hydrogen in a weight ratio of 30:90 to 70:10, specifically, 40:60 to 60:40, and more specifically, 45:75 to 55:25.
[0060] When the polyolefin block contains a structure in which R1 in formula (a) is hydrogen and a structure in which R1 has a substituent other than hydrogen within the above range, the block copolymer produced contains an appropriate amount of branches in the structure, and therefore has a high 300% modulus value and elongation at break value, and can exhibit excellent elastic properties. In addition, the block copolymer can have a wide molecular weight distribution along with a high molecular weight, and therefore has excellent processability.
[0061] In addition, the first polystyrene block of the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition of the present invention may contain one or more repeating units represented by the following chemical formula c.
[0062] [ka]
[0063] In the above chemical formula c, R2 is an aryl having 6 to 20 carbon atoms; or an aryl having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; l is independently an integer from 10 to 1,000.
[0064] The R2 may be phenyl; or phenyl unsubstituted or substituted with halogen, alkyl having 1 to 8 carbon atoms, cycloalkyl having 3 to 12 carbon atoms, alkoxy having 1 to 8 carbon atoms, or aryl having 6 to 12 carbon atoms, or the R2 may be phenyl.
[0065] The 1 may be an integer of 10 to 1,000, specifically, an integer of 50 to 700. When the 1 is within the above range, the viscosity of the polyolefin-polystyrene block copolymer produced by the production method of the present invention may be at an appropriate level.
[0066] In particular, in the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition of the present invention, the polyolefin block containing the repeating unit represented by the chemical formula a and the first polystyrene block containing the repeating unit represented by the chemical formula c may be bonded to each other to form a composite block represented by the following chemical formula d.
[0067] [ka]
[0068] In the above chemical formula d, R1 is hydrogen; an alkyl having 1 to 20 carbon atoms; an alkyl having 1 to 20 carbon atoms substituted with a silyl group; an arylalkyl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms substituted with a silyl group; R2 is an aryl having 6 to 20 carbon atoms; or an aryl having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; l is an integer from 10 to 1,000; n is an integer from 1 to 10,000.
[0069] In addition, in the above chemical formula d, R1, R2, l and n are as defined in the above chemical formulae a and c, respectively.
[0070] In addition, when the polyolefin block contains a repeating unit represented by the formula a, a composite block formed by binding a first polystyrene block containing a repeating unit represented by the formula c may be represented by the following formula e.
[0071] [ka]
[0072] In the chemical formula e, R1', R1'', R2, p, l and n' are as defined in the chemical formula a or c, respectively.
[0073] In addition, in one embodiment of the present invention, during the preparation of the polyolefin-polystyrene multiblock copolymer, a styrene monomer forms a polyolefin block, and the styrene monomer is bound to an organozinc compound and polymerized to form another styrene polymer block. In this specification, the other styrene polymer block is referred to as a second polystyrene block. The second polystyrene block may include a repeating unit represented by the following chemical formula f.
[0074] [ka]
[0075] In the above chemical formula f, R3 is an aryl having 6 to 20 carbon atoms; or an aryl having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; m is independently an integer from 10 to 1,000.
[0076] According to one embodiment of the present invention, R3 may be phenyl; or phenyl substituted or unsubstituted with halogen, alkyl having 1 to 8 carbon atoms, cycloalkyl having 3 to 12 carbon atoms, alkoxy having 1 to 8 carbon atoms, or aryl having 6 to 12 carbon atoms, and R3 may be phenyl.
[0077] The above m is an integer of 10 to 1,000, and specifically, can be an integer of 50 to 700.
[0078] That is, the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition of the present invention may contain a first polystyrene block containing a repeating unit represented by the chemical formula c, and a second polystyrene block represented by the chemical formula f.
[0079] Therefore, the block copolymer composition may include a triblock copolymer including a polyolefin block including one or more repeating units represented by the following chemical formula a, a first polystyrene block including a repeating unit represented by the following chemical formula c, and a second polystyrene block including a repeating unit represented by the following chemical formula f.
[0080] [ka]
[0081] [ka]
[0082] [ka]
[0083] In the above chemical formula, R1 is hydrogen; an alkyl having 1 to 20 carbon atoms; an alkyl having 1 to 20 carbon atoms substituted with a silyl group; an arylalkyl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms substituted with a silyl group; R2 and R3 are an aryl having 6 to 20 carbon atoms; or an aryl having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; n is an integer from 10 to 10,000; l and m are each independently an integer of 10 to 1,000.
[0084] In addition, in the above chemical formula, R1, R2, R3, n, l and m are as defined in the above chemical formulas a, c and f, respectively.
[0085] Method for producing polyolefin-polystyrene multiblock copolymer The method for producing the polyolefin-polystyrene multiblock copolymer includes the steps of: (S1) forming a polyolefin block by polymerizing an olefin monomer using an organozinc compound as a chain transfer agent in the presence of a catalyst composition including a transition metal compound represented by the following chemical formula 1; and (S2) forming a polystyrene block by anionically polymerizing the polyolefin block and a styrene monomer in the presence of an alkyllithium compound containing a silicon atom and a triamine compound.
[0086] The method for producing the polyolefin-polystyrene multiblock copolymer, as described below, is to form a polyolefin chain using a transition metal compound represented by Chemical Formula 1, which is efficiently used in the polymerization of an olefin monomer, as a catalyst, and then perform styrene anion polymerization to form a polyolefin-polystyrene block, thereby forming a polyolefin-polystyrene multiblock copolymer having a specific tan δ peak height and half-width of the tan δ peak.
[0087] Step (S1) Step (S1) is a step of polymerizing an olefin monomer using an organozinc compound as a chain transfer agent in the presence of a catalyst composition containing a transition metal compound represented by the following chemical formula 1 to form a polyolefin block.
[0088] [ka]
[0089] In the above Chemical Formula 1, R1~R 11 each independently represents hydrogen; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an arylalkoxy group having 7 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylalkyl group having 7 to 20 carbon atoms, The R1 to R 11 two or more adjacent rings among these may be linked to each other to form an aliphatic ring having 3 to 20 carbon atoms or an aromatic ring having 6 to 20 carbon atoms; X1 and X2 are each independently hydrogen; a halogen; a hydroxy group; an amino group; a thio group; a silyl group; a cyano group; a nitro group; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an arylalkyl group having 7 to 20 carbon atoms; a heteroaryl group having 5 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; an alkylamino group having 1 to 20 carbon atoms; an arylamino group having 6 to 20 carbon atoms; an alkylthio group having 1 to 20 carbon atoms; an arylthio group having 6 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylsilyl group having 6 to 20 carbon atoms.
[0090] When polymerization is carried out in the presence of an excess amount of a chain transfer agent (e.g., (Et)2Zn) relative to the catalyst, olefin polymer chains grow uniformly from dialkylzinc through rapid alkyl exchange between zinc (Zn) and hafnium (Hf), achieving living polymerization, which is called coordinate chain transfer polymerization (CCTP). Conventional metallocene catalysts are unable to carry out living polymerization through the β-elimination process, and the few catalysts known to be applicable to CCTP are only capable of homopolymerization of ethylene, making it very difficult to copolymerize ethylene and alpha-olefins through CCTP. Therefore, it has been very difficult to produce block copolymers through living polymerization through CCTP using general transition metal compounds as catalysts.
[0091] Meanwhile, the hafnium compound represented by the above formula 1 includes a 1,2,3,4-tetrahydro-1,10-phenanthroline skeleton and a Hf-C(aryl) bond [N amido ,N,C aryl ]HfMe2-type complex, which shows excellent alpha-olefin incorporation ability in the polymerization reaction of ethylene and alpha-olefin, and in particular, the molecular weight of the olefin polymer and the content of alpha-olefin vary depending on the content of the chain transfer agent, which indicates that the compound was successfully used in CCTP and β-elimination reaction hardly occurred to a negligible extent. That is, it is possible to carry out living polymerization by copolymerizing ethylene and alpha-olefin monomers in CCTP using the hafnium compound represented by Chemical Formula 1, and to successfully produce block copolymers having various block compositions.
[0092] In addition, it is possible to synthesize polyolefin-polystyrene block copolymers by converting CCTP using the hafnium compound into an anionic styrene polymerization reaction. Thus, the hafnium compound can be usefully used as a catalyst for the production of olefin polymers, which is a unique feature that can be achieved by the novel structure of the hafnium compound represented by Chemical Formula 1.
[0093] Specifically, in the above Chemical Formula 1, the R 11 may each independently be hydrogen; an alkyl group having 1 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; or an aryl group having 6 to 20 carbon atoms, and preferably, R 10 is hydrogen and at the same time R 11 can be hydrogen; an alkyl group having 1 to 20 carbon atoms; or an aryl group having 6 to 20 carbon atoms, and more preferably, R 10 is hydrogen and at the same time R 11 can be hydrogen; or an alkyl group having 1 to 20 carbon atoms.
[0094] Or, in the above Chemical Formula 1, the R1 to R 11 may each independently be hydrogen; an alkyl group having 1 to 20 carbon atoms; or an aryl group having 6 to 20 carbon atoms, in which case R3 and R4 may be linked to each other to form an aromatic ring having 5 to 20 carbon atoms, for example, a benzene ring, and preferably R3 and R4 are linked to each other to form a benzene ring, and R 11 can be an alkyl group having 1 to 20 carbon atoms; or an aryl group having 6 to 20 carbon atoms.
[0095] Alternatively, in the above Chemical Formula 1, R1, R2, and R5 to R 10 is hydrogen; and R, R and R 11 are each independently a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, and R3 and R4 can be linked to each other to form an aromatic ring having 5 to 20 carbon atoms, such as a benzene ring.
[0096] On the other hand, X1 and X2 may each independently represent hydrogen; an alkyl group having 1 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; or an aryl group having 6 to 20 carbon atoms, and preferably each independently represent an alkyl group having 1 to 20 carbon atoms, and X1 and X2 may be the same as each other.
[0097] In the present invention, "alkyl" means a straight or branched chain hydrocarbon residue.
[0098] In the present invention, "alkenyl" means a straight or branched chain alkenyl group.
[0099] In the present invention, "aryl" preferably has 6 to 20 carbon atoms, and specific examples thereof include, but are not limited to, phenyl, naphthyl, anthracenyl, pyridyl, dimethylanilinyl, and anisolyl.
[0100] In the present invention, "alkylaryl" means an aryl group substituted with an alkyl group as defined above.
[0101] In the present invention, "arylalkyl" means an alkyl group substituted with the above-mentioned aryl group.
[0102] In the present invention, the "alkylsilyl" can be a silyl substituted with an alkyl having 1 to 20 carbon atoms, and can be, for example, trimethylsilyl or triethylsilyl.
[0103] In the present invention, "alkylamino" refers to an amino group substituted with the above-mentioned alkyl group, and examples thereof include, but are not limited to, a dimethylamino group and a diethylamino group.
[0104] In the present invention, unless otherwise specified, "hydrocarbyl" refers to a monovalent hydrocarbon group having 1 to 20 carbon atoms and consisting only of carbon and hydrogen, such as alkyl, aryl, alkenyl, alkynyl, cycloalkyl, alkylaryl, or arylalkyl, regardless of its structure.
[0105] More specifically, the hafnium compound represented by the formula 1 may be a hafnium compound represented by the following formula 1a or 1b:
[0106] [ka]
[0107] [ka]
[0108] In the above Chemical Formula 1a and Chemical Formula 1b, R 11 is hydrogen; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an arylalkoxy group having 7 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylalkyl group having 7 to 20 carbon atoms, X1 and X2 are each independently hydrogen; a halogen; a hydroxy group; an amino group; a thio group; a silyl group; a cyano group; a nitro group; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an arylalkyl group having 7 to 20 carbon atoms; a heteroaryl group having 5 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; an alkylamino group having 1 to 20 carbon atoms; an arylamino group having 6 to 20 carbon atoms; an alkylthio group having 1 to 20 carbon atoms; an arylthio group having 6 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylsilyl group having 6 to 20 carbon atoms.
[0109] The hafnium compound may be specifically represented by any one of the following formulas 1-1 to 1-5, but is not limited thereto, and all hafnium compounds corresponding to formula 1 are included in the present invention.
[0110] [ka]
[0111] [ka]
[0112] [ka]
[0113] [ka]
[0114] [ka]
[0115] The hafnium compound of the present invention can be prepared by reacting a compound represented by the following Chemical Formula 2 and a compound represented by the following Chemical Formula 3.
[0116] [ka]
[0117] [Chemical formula 3] Hf(X1X2)2
[0118] In the above chemical formula, R1~R 11 , X1 and X2 are defined as above.
[0119] Meanwhile, when preparing the hafnium compound represented by Formula 1, the step of preparing the ligand compound can be performed in different ways according to the structure of the final hafnium compound, as follows:
[0120] For example, in the ligand compound, R3 and R4 do not form a ring with each other, and R 11 When is a hydrogen atom, a ligand compound is prepared by hydrogenating it in the presence of a ruthenium catalyst as shown below, and then the ligand compound is reacted with a compound represented by Chemical Formula 3, which is a hafnium precursor, to prepare a hafnium compound.
[0121] [ka]
[0122] In addition, in the ligand compound structure, R3 and R4 do not form a ring with each other, and R 11 When R is a substituent rather than a hydrogen atom, an organolithium compound can be used to convert R 11 is first introduced, and then hydrogenated in the presence of a ruthenium catalyst to produce a ligand compound.
[0123] [ka]
[0124] In the ligand compound structure, R3 and R4 are linked together to form an aromatic ring having 5 to 20 carbon atoms, and R 11 When R is not a hydrogen atom but a substituent, an organolithium compound can be used to convert R 11 can be first introduced, and then hydrogenated under Pd / C catalyst to produce the ligand compound in order to prevent hydrogenation of aromatic rings such as naphthyl groups.
[0125] [ka]
[0126] That is, the hafnium compound can be prepared by alkylating and hydrogenating a precursor compound of the ligand compound under suitable reagents and reaction conditions to prepare a ligand compound, and then introducing hafnium thereto. The specific type of alkylating reagent, reaction temperature, and pressure can be appropriately changed by a person skilled in the art in consideration of the structure of the final compound and the experimental conditions.
[0127] In the present invention, the organozinc compound is a substance that is used as a chain transfer agent to induce chain transfer during polymerization reaction to produce a copolymer, and specifically, may be a compound represented by the following Chemical Formula 4.
[0128] [ka]
[0129] In the above Chemical Formula 4, A is an alkylene having 1 to 20 carbon atoms; an arylene having 6 to 20 carbon atoms; or an arylene having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; B is an aryl having 6 to 12 carbon atoms substituted with an alkenyl having 2 to 12 carbon atoms. In addition, A may be an alkylene having 1 to 12 carbon atoms; an arylene having 6 to 12 carbon atoms; or an arylene having 6 to 12 carbon atoms substituted with halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; The B may be an aryl having 6 to 12 carbon atoms substituted with an alkenyl having 2 to 8 carbon atoms.
[0130] The formula 4 may have a structure in which both ends of the formula are double bonds. For example, when the B is an aryl substituted with an alkenyl, the aryl is connected to the A, and the double bond of the alkenyl substituted with the aryl may be located at the outermost portion in the formula 4.
[0131] When the organozinc compound is reacted with one or more olefinic monomers in the presence of a catalyst composition, the olefinic monomer may be inserted between the zinc (Zn) of the organozinc compound and the organic group (A) to perform polymerization.
[0132] The organozinc compound may be mixed in an amount of 1 to 200 equivalents relative to 1 equivalent of the transition metal compound of Formula 1, specifically, in an amount of 10 to 100 equivalents relative to 1 equivalent of the transition metal compound of Formula 1.
[0133] The organozinc compound does not contain impurities such as THF and large amounts of magnesium salts and can be provided in high purity, which makes it usable as a chain transfer agent and advantageous for use in olefin polymerization.
[0134] The catalyst composition may further include a co-catalyst compound, which serves to activate the transition metal compound represented by Formula 1. The co-catalyst may be one known in the art, and may be one or more selected from the following Formulas 5 to 7:
[0135] [Chemical formula 5] -[Al(R a )-O] m -
[0136] [Chemical formula 6] D(R a )3
[0137] [Chemical formula 7] [LH] + [Z(A)4] - or [L] + [Z(A)4] -
[0138] In the above formula, R a each independently represents a halogen group; a hydrocarbyl group having 1 to 20 carbon atoms; or a hydrocarbyl group substituted with a halogen and having 1 to 20 carbon atoms, m is an integer of 2 or more, D is aluminum or boron; L is a neutral or cationic Lewis acid; Z is a group 13 element, Each A is independently an aryl having 6 to 20 carbon atoms, in which one or more hydrogen atoms may be substituted by a substituent; or an alkyl having 1 to 20 carbon atoms, The substituent of A is a halogen; a hydrocarbyl having 1 to 20 carbon atoms; an alkoxy having 1 to 20 carbon atoms; or an aryloxy having 6 to 20 carbon atoms.
[0139] The compound represented by Chemical Formula 5 is not particularly limited as long as it is an alkylaluminoxane. Preferred examples include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, and butylaluminoxane, and a particularly preferred compound is methylaluminoxane.
[0140] The compound represented by Chemical Formula 6 is not particularly limited, but preferred examples include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylchloroaluminum, triisopropylaluminum, tri-s-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, and tributylboron. Particularly preferred compounds are selected from trimethylaluminum, triethylaluminum, and triisobutylaluminum.
[0141] An example of the compound represented by the formula 7, when Z is boron, is, for example, dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] -, dioctadecylmethylammonium tetrakis(phenyl)borate, dioctadecylmethylammonium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate, triethylammonium tetraphenylborate, tributylammonium tetraphenylborate, trimethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, trimethylammonium tetra(p-tolyl)borate, trimethylammonium tetra(o,p-dimethylphenyl)borate, tributylammonium tetra(p-trifluoromethylphenyl)borate, trimethylammonium tetra(p-trifluoromethylphenyl)borate, tributylammonium tetrapentafluorophenylborate, N,N-diethylanilinium tetrapentylborate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrapentafluorophenylborate, diethylammonium tetrapentafluorophenylborate, triphenylphosphonium tetraphenylborate, trimethylphosphonium tetraphenylborate, Z can be, for example, triethylammonium tetraphenylaluminum, tributylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetrapentafluorophenylaluminum, N,N-diethylanilinium tetraphenylaluminum, N,The compound may be, but is not limited to, N-diethylanilinium tetrapentafluorophenylaluminum, diethylammonium tetrapentafluorophenylaluminum, triphenylphosphonium tetraphenylaluminum, trimethylphosphonium tetraphenylaluminum, or a combination thereof.
[0142] In particular, the co-catalyst used in the present invention may be a compound represented by Chemical Formula 7, specifically, dioctadecylmethylammonium dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate.
[0143] In addition, the cocatalyst used in the present invention may be prepared from an anhydrous hydrocarbon solvent. For example, the hydrocarbon solvent may be at least one selected from the group consisting of butane, pentane, neopentane, hexane, cyclohexane, methylcyclohexane, heptane, octane, benzene, toluene, xylene, and ethylbenzene, but is not limited thereto, and all hydrocarbon solvents available in the art may be used in an anhydrous form.
[0144] In the present invention, when the co-catalyst is produced in an anhydrous hydrocarbon solvent, 1 In the H NMR spectrum, at least one peak is shown in the range of 1.75 ppm to 1.90 ppm and at least one peak is shown in the range of 1.90 ppm to 2.00 ppm. This is because the protons attached to the α-carbon adjacent to the nitrogen, sulfur, or phosphorus contained in L each show a different peak. For example, if the compound represented by chemical formula 1 is [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] - If so, then 1 In the H NMR spectrum, the two protons present in NCH2 can each show a different signal.
[0145] In addition, the hafnium compound represented by Formula 1 and the co-catalyst may be used in a form supported on a carrier. The carrier may be, but is not limited to, silica or alumina.
[0146] The olefin monomer input as a reactant in step (S1) may be ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, or a mixture thereof. The olefin monomer may be used alone or in combination of two or more.
[0147] The step (S1) may be carried out, for example, in a homogeneous solution state. In this case, the solvent may be a hydrocarbon solvent or an olefin monomer itself. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents having 4 to 20 carbon atoms, specifically, isobutane, hexane, cyclohexane, methylcyclohexane, etc. The solvent may be used alone or in combination of two or more.
[0148] The polymerization temperature in step (S1) may vary depending on the reactants, reaction conditions, etc., but may be 70 to 170° C., more specifically, 80 to 150° C., or 90 to 120° C. Within this range, the solubility of the polymer can be increased and the catalyst can be thermally stabilized.
[0149] The polymerization of step (S1) can be carried out batchwise, semi-continuously or continuously, and can also be carried out in two or more steps having different reaction conditions.
[0150] The compound prepared in the above step (S1) can serve as a precursor for preparing the polyolefin-polystyrene multiblock copolymer of the present invention through an anionic polymerization reaction in the below-described step (S2).
[0151] Step (S2) The step (S2) is a step of preparing a polyolefin-polystyrene multiblock copolymer by anionically polymerizing the polyolefin block and a styrene monomer in the presence of an alkyllithium compound containing a silicon atom and a triamine compound, successively to the step (S1), to form a polystyrene block.
[0152] In the step (S2), the styrene monomer can be continuously inserted between the zinc-carbon bonds of (polyolefinnyl)2Zn contained in the compound formed by the above step (S1), and at the same time, the styrene group present in the end group of the compound formed by the step (S1) can participate as a copolymerization site with the styrene monomer and be linked to the polystyrene chain. In addition, the multiblock copolymer produced by the above process can be easily quenched by reacting the end group with water, oxygen or organic acid, thereby being converted into an industrially useful polyolefin-polystyrene multiblock copolymer.
[0153] The styrene-based monomer may be a styrene-based monomer having 6 to 20 carbon atoms. More specifically, it may be a styrene-based monomer including ethylene substituted with an aryl group having 6 to 20 carbon atoms, ethylene substituted with a phenyl group, etc., such as styrene.
[0154] The silicon-containing alkyllithium compound may be a compound represented by the following formula 8:
[0155] [Chemical formula 8] (CH3)3Si(CH2)Li
[0156] Such silicon-containing alkyllithium compounds are widely used as initiators for anionic polymerization and are readily available, and can be easily utilized in the present invention.
[0157] The triamine compound may be a compound represented by the following Formula 9.
[0158] [ka]
[0159] The triamine compound is a compound that coordinates well with lithium and is used for the purpose of improving the reactivity of the alkyllithium compound as a base or as a nucleophile, and is easily available and low cost.
[0160] In the present invention, the compounds of the chemical formulas 8 and 9 (e.g., Me3SiCH2Li·(PMDETA)) are newly used as initiators in step (S2) to suppress the production of polystyrene homopolymers, polyolefin homopolymers, and polyolefin-polystyrene double block copolymers, while maximizing the production of polyolefin-polystyrene multiblock copolymers, which is the objective of the present invention.
[0161] The silicon-containing alkyllithium compound represented by Chemical Formula 8 and the triamine compound represented by Chemical Formula 9 may be mixed in an aliphatic hydrocarbon solvent and then charged, or the silicon-containing alkyllithium compound represented by Chemical Formula 8 and the triamine compound represented by Chemical Formula 9 may be charged in sequence into a reactor.
[0162] The anionic polymerization temperature in step (S2) may vary depending on the reactants, reaction conditions, etc., but may be specifically 40 to 170°C, more specifically 60 to 150°C, or 90 to 100°C.
[0163] The anionic polymerization in step (S2) can be carried out batchwise, semi-continuously or continuously, and can also be carried out in two or more steps having different reaction conditions.
[0164] The anionic polymerization time in step (S2) may vary depending on the reactants, reaction conditions, etc., and may be specifically 0.5 to 10 hours, 1 to 8 hours, 2 to 7 hours, or 4 to 6 hours. Within the above range, it is advantageous to convert all of the styrene-based monomer added into a multiblock copolymer.
[0165] In this manner, in the production method of the present invention, a polyolefin-polystyrene-based multiblock copolymer is produced by growing a polyolefin chain by olefin polymerization using an organozinc compound represented by the above-mentioned chemical formula 4, followed by continuous styrene anionic polymerization. This makes it possible to efficiently produce a polyolefin-polystyrene-based multiblock copolymer that has improved physical properties compared to conventional methods and is easily applicable in industry.
[0166] The method for producing a polyolefin-polystyrene-based multiblock copolymer according to one embodiment of the present invention is characterized in that it is produced by a route different from the conventional method for producing a polyolefin-polystyrene-based multiblock copolymer, which is a two-step process of anionic polymerization of styrene and diene followed by hydrogenation, without a hydrogenation reaction of the double bonds in the main chain of the copolymer. Therefore, the polyolefin-polystyrene-based multiblock copolymer contained in the thermoplastic resin composition of the present invention is characterized in that it does not contain unsaturated bonds that are not saturated during the hydrogenation process of the double bonds in the main chain.
[0167] Meanwhile, the thermoplastic resin composition according to an embodiment of the present invention having the above-mentioned configuration may contain each component in an appropriate content so as to satisfy its intended use and the physical properties required therefor. For example, in the present invention, the thermoplastic resin composition may contain the (1) polypropylene and the (2) polyolefin-polystyrene multiblock copolymer in a weight ratio of 10:90 to 90:10, specifically, in a weight ratio of 20:80 to 80:20, and more specifically, in a weight ratio of 40:60 to 60:40.
[0168] If the content of the polyolefin-polystyrene multiblock copolymer contained in the thermoplastic resin composition is too low, the impact strength may be reduced, and if the content of the polyolefin-polystyrene multiblock copolymer is too high, the fluidity of the thermoplastic resin composition may be reduced. The mixing ratio can be controlled in consideration of the distinctive physical properties of the polypropylene and the polyolefin-polystyrene multiblock copolymer.
[0169] The thermoplastic resin composition according to one embodiment of the present invention may further include, in addition to the polypropylene and the polyolefin-polystyrene multiblock copolymer, an inorganic filler for improving the mechanical properties of the thermoplastic resin composition.
[0170] Specifically, the inorganic filler may be a powdered filler, a flake-like filler, a fibrous filler, or a balloon-like filler, and any one or a mixture of two or more of these may be used. Specifically, the powdered filler may be natural silicic acid or silicate such as unpowdered talc, kaolinite, plastic clay, or sericite; carbonate such as precipitated calcium carbonate, heavy calcium carbonate, or magnesium carbonate; hydroxide such as aluminum hydroxide or magnesium hydroxide; oxide such as zinc oxide, magnesium oxide, or titanium oxide; synthetic silicic acid or silicate such as calcium silicate hydrate, aluminum silicate hydrate, silicic acid hydrate, or silicic anhydride; silicon carbide, etc. Also, the flake-like filler may be mica, etc. Also, the fibrous filler may be basic magnesium sulfate whisker, calcium titanate whisker, aluminum borate whisker, sepiolite, PMF (Processed Mineral Fiber), or potassium titanate, etc. Also, the balloon-like filler may be glass balloon, etc. Among them, talc may be used.
[0171] The inorganic filler may be surface-treated in order to improve the strength properties and moldability of the thermoplastic resin composition.
[0172] Specifically, the surface may be physically or chemically treated using a surface treatment agent such as a silane coupling agent, a higher fatty acid, a fatty acid metal salt, an unsaturated organic acid, an organic titanate, a resin acid, or polyethylene glycol.
[0173] The inorganic filler has an average particle size (D 50) may be 1 μm to 20 μm, specifically 3 μm to 15 μm, and more specifically 5 μm to 10 μm. If the average particle size of the inorganic filler is too small, it may be difficult to uniformly disperse the inorganic filler when mixed with polypropylene and polyolefin-polystyrene multiblock copolymers due to aggregation between the inorganic filler particles, and as a result, the effect of improving the mechanical properties of the thermoplastic resin composition may be little. In addition, if the average particle size of the inorganic filler is too large, there is a risk of a decrease in physical properties due to a decrease in the dispersibility of the inorganic filler itself.
[0174] In the present invention, the average particle diameter (D 50 ) can be defined as the particle size at 50% of the particle size distribution. In the present invention, the average particle size (D 50 ) can be measured, for example, by electron microscopy using a scanning electron microscopy (SEM) or a field emission scanning electron microscopy (FE-SEM), or by the laser diffraction method. More specifically, when measuring by the laser diffraction method, the inorganic filler particles are dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and the average particle diameter (D) at 50% of the particle size distribution in the measuring device is measured. 50 ) can be calculated.
[0175] The inorganic filler may be contained in an amount of 0.1 to 40 parts by weight based on 100 parts by weight of the thermoplastic resin composition. If the content of the inorganic filler in the thermoplastic resin composition is less than 0.1 parts by weight based on 100 parts by weight of the thermoplastic resin composition, the improvement effect due to the inclusion of the inorganic filler is not significant, and if it exceeds 40 parts by weight, the processability of the thermoplastic resin composition may be reduced. More specifically, the inorganic filler may be contained in an amount of 0.1 to 20% by weight based on the total weight of the thermoplastic resin composition.
[0176] The thermoplastic resin composition according to an embodiment of the present invention, which satisfies the above-mentioned composition and content requirements, may be prepared by adding polypropylene and optionally an inorganic filler to a polyolefin-polystyrene multiblock copolymer, followed by heat treatment, where the type and content of the polypropylene are as described above.
[0177] The mixing step can be carried out by a conventional method, specifically, a super mixer or a ribbon mixer can be used for the mixing.
[0178] In addition, during the mixing process, additives such as antioxidants, heat stabilizers, UV stabilizers, antistatic agents, etc. may be further included as necessary, and a small amount of an adhesive resin or an additive having a polar group may be selectively further used within an appropriate content range in order to improve coating properties.
[0179] The heat treatment process may be performed at a temperature of from the melting point of polypropylene to 210° C. The heat treatment process may be performed using various compounding machines such as a conventional twin-screw extruder, a single-screw extruder, a roll mill, a kneader, or a Banbury mixer.
[0180] The thermoplastic resin composition according to one embodiment of the present invention produced by the above-mentioned production method has excellent elongation and tensile strength, and can also exhibit high fluidity.
[0181] Specifically, the thermoplastic resin composition can satisfy the following physical properties (A) to (D). (A) Shore A hardness 1 to 90, (B) Compression set is 0 to 80%. (C) Melt flow rate (MFR, 230°C, 2.16 kg) is 0.1 to 300 g / 10 min; (D) Melt flow rate (MFR, 230°C, 5 kg) is 0.1 to 500 g / 10 min.
[0182] (A) The Shore A hardness can be 1-90, specifically 10-90, and more specifically 20-90.
[0183] The shore A hardness can be measured in accordance with ASTM D2240.
[0184] (B) The compression set can be from 0 to 80%, specifically from 1 to 80%, and more specifically from 10% to 70%.
[0185] The compression set can be measured in accordance with ASTM D-3574.
[0186] (C) The melt flow rate (MFR, 230°C, 2.16 kg) can be 0.1 to 300 g / 10 min, specifically 0.2 to 200 g / 10 min, and more specifically 0.5 to 100 g / 10 min.
[0187] (D) The melt flow rate (MFR, 230°C, 5 kg) can be 0.1 to 500 g / 10 min, specifically 0.5 to 300 g / 10 min, and more specifically 2 to 150 g / 10 min.
[0188] The melt flow rates were measured according to ASTM-D 1238 under conditions of 230° C. and a load of 2.16 kg and 230° C. and a load of 5 kg, respectively.
[0189] INDUSTRIAL APPLICABILITY The thermoplastic resin composition according to one embodiment of the present invention is useful for blow molding, extrusion molding or injection molding in various fields and applications such as various packaging applications, construction applications, daily necessities, etc., for materials for automobiles, electric wires, toys, fibers, or medical applications, and in particular, has excellent physical properties such as heat resistance, rigidity, as well as excellent toughness and impact strength at room temperature and at low temperatures, and can be usefully used for interior and exterior parts of automobiles.
[0190] According to another embodiment of the present invention, there is provided a molded article and an automobile part manufactured using a thermoplastic resin composition satisfying the above-mentioned physical property requirements.
[0191] Specifically, the molded product may be a blow molding, an inflation molding, a cast molding, an extrusion laminate molding, an extrusion molding, a foam molding, an injection molding, a sheet, a film, a fiber, a monofilament, or a nonwoven fabric.
[0192] The automobile parts may be automobile interior / exterior materials, etc.
[0193] Working Example The present invention will be described in more detail with reference to the following examples. However, the following examples are for illustrating the present invention and are not intended to limit the scope of the present invention.
[0194] <Production of transition metal compounds> Manufacturing Example 1 (i) Preparation of Ligand Compound Isopropyllithium (0.45 mL, 0.36 mmol, 0.79 M in pentane) was slowly added to 2-naphthyl-1,10-phenanthroline (0.789 g, 2.58 mmol) in toluene (8 mL) at -10 °C. After stirring at room temperature for 3 h, degassed H2O (3 mL) was added. The aqueous layer was removed with a syringe under N2. The solvent was removed using a vacuum line and the residue was dissolved in degassed ethanol (15 mL) and THF (5 mL). The solution was transferred under N2 to a bomb reactor containing Pd / C (0.242 mmol, 10 mol%). After charging with H2 gas at 5 bar, it was stirred at room temperature for 12 h. The H2 gas was released and the catalyst residue was removed by filtration over Celite. The solvent was removed and the residue was purified by silica gel column chromatography using ethyl acetate / hexane (1 / 3, v / v). A pale yellow sticky solid was obtained (0.085g, 73%). 1 H NMR and 13 The C NMR spectrum is shown in Figure 1.
[0195] - 1 H NMR(C6D6): δ 8.58(d, J = 7.8 Hz, H), 7.75(d, J = 9.0 Hz, H), 7.70(d, J = 9.6 Hz, H), 7.66(d, J = 7.2 Hz, H), 7.63(d, J = 6.6 Hz, H), 7.32(m, 4H), 7.18(d, J = 8.4 Hz, H), 6.99(d, J = 7.8 Hz, H), 6.39(s, H, NH), 2.93(m, H), 2.79(m, H), 2.70(dt, J = 4.8 Hz, H), 1.70(m, H), 1.63(m, H), 1.47(m, H), 0.81(d, J = 7.2 Hz, 3H, CH(CH3)2), 0.76(d, J = 7.2 Hz, 3H, CH(CH3)2) ppm. - 13 C{ 1H} NMR(C6D6): δ 18.34, 18.77, 24.43, 26.78, 32.52, 56.73, 112.78, 116.67, 122.62, 125.59, 126.10, 126.51, 126.61, 126.86, 128.14, 128.69, 129.03, 129.28, 132.20, 134.71, 136.41, 137.64, 139.79, 141.75, 155.92 ppm. - m / z calculation([M + ] C 25 H 24 N2) 352.4800. Found: 352.1942.
[0196] (ii) Preparation of transition metal compounds [ka]
[0197] MeMgBr (1.24 mL, 3.11 M in diethyl ether) was added dropwise to a stirred suspension of HfCl4 (0.300 g, 0.938 mmol) in toluene (8 mL) at -78 °C. After stirring for 1 h at a temperature range of -40 °C and -35 °C, the solution was cooled back to -78 °C. A solution (0.24 g, 0.94 mmol) of the ligand compound (0.366 g, 1.00 mmol) in toluene (4 mL) was added dropwise. The resulting solution was stirred for 2 h at a controlled temperature range of -40 °C and -35 °C, and then stirred overnight at room temperature. The solvent was removed using a vacuum line and the residue was extracted with toluene (50 mL). Trituration with hexane gave a dark brown powder (0.226 g, 47%). 1 H NMR and 13 The C NMR spectrum is shown in Figure 2.
[0198] - 1H NMR(C6D6): δ 8.66(d, J = 7.8 Hz, H), 8.50(d, J = 7.8 Hz, H), 7.92(d, J = 9.0 Hz, H), 7.83(d, J = 7.2 Hz, H), 7.76(d, J = 8.4 Hz, H), 7.62(d, J = 7.8 Hz, H), 7.40(td, J = 7.2 Hz, H), 7.32(m, H), 7.14(d, J = 7.8 Hz, H), 6.77(d, J = 7.2 Hz, H), 4.02(m, H), 2.80(m, H), 2.62(dt, J = 6.0 Hz, H), 2.55(m, H), 1.88(m, H), 1.72(m, H), 1.09 and 1.04(d, J = 6.6 Hz, 6H, CH(CH3)2), 0.82(s, 3H, HfCH3), 0.81(s, 3H, HfCH3) ppm. - 13 C{ 1 H} NMR(C6D6): δ 18.55, 21.28, 23.07, 25.44, 32.58, 60.98, 63.06, 66.88, 112.37, 119.64, 120.21, 124.55, 125.48, 126.81, 126.97, 129.31, 129.97, 130.26, 131.25, 133.82, 135.51, 140.97, 141.44, 143.94, 150.14, 164.58, 209.13 ppm. - Analysis (calculation) (C 27 H 28 HfN2): C, 58.01; H, 5.05; N, 5.01%. - Measurement: C, 57.91; H, 5.01; N, 5.11%.
[0199] <Production of promoter> Excessive K + [B(C6F5)4] - (0.633 g, 0.881 mmol, assumed to be pure) was dissolved in toluene (anhydrous, 10 mL) in [(C 18 H 37)2N(H)Me] + [Cl] - (0.404 g, 0.705 mmol) for 1 h at room temperature in a glove box. After filtration over Celite, the solvent was removed using a vacuum line. The residue was dissolved in methylcyclohexane (4 mL) and filtered over Celite again. The solvent was removed to yield a yellow oily compound which was used without further purification (0.797 g, 93%).
[0200] - 1 H NMR(C6D6): δ 3.15(br, H, NH), 1.97(m, 2H, NCH2), 1.80(m, H, NCH2), 1.51(d, J = 6.0 Hz, 3H, NCH3), 1.45-1.29(m, 48H), 1.26(quintet, J = 7.2 Hz, 4H), 1.13(quintet, J = 7.2 Hz, 4H), 0.94(t, J = 7.8 Hz, 6H), 0.88(quintet, J = 7.8 Hz, 4H), 0.81(m, 4H) ppm. - 19 F NMR(C6D6): δ -132.09, -161.75, -165.98.
[0201] <Production of organic zinc compounds> [ka]
[0202] Borane dimethyl sulfide (1.6 mL, 3.2 mmol) was gradually added to triethylborane (0.6 g) while stirring, and the mixture was allowed to react for 90 minutes. The mixture was gradually added to divinylbenzene (3.8 g) dissolved in anhydrous diethyl ether (10 mL) cooled to -20°C, and the mixture was allowed to stir overnight. After removing the solvent using a vacuum pump, diethylzinc (0.8 g) was added. The reaction was continued at 0°C for 5 hours while removing the triethylborane produced by distillation under reduced pressure. Excess divinylbenzene and diethylzinc were removed by distillation under reduced pressure at 40°C. Methylcyclohexane (150 mL) was added to dissolve the product again, and the solid compound produced as a by-product was removed by filtration using Celite to produce the organozinc compound represented by the above chemical formula.
[0203] <Production of polyolefin-polystyrene multiblock copolymer> Example 1 A Parr reactor (1 gallon) was vacuum dried for 2 hours at 120° C. A solution of Oc3Al (trioctyl aluminum, 1466.4 mg, 1,000 μmol Al) in methylcyclohexane (1,200 g) was added to the reactor. The mixture was stirred at 120° C. for 1 hour using a heating jacket, and then the solution was removed using a cannula.
[0204] The reactor was filled with methylcyclohexane (600 g) containing Oc3Al (715.6 mg, 488 μmol-Al / 25 wt% in hexane) as a scavenger, 1-hexene (280 g) as an olefin monomer, and the temperature was set to 90° C. A solution of the organozinc compound (3,000 μmol) in methylcyclohexane (3.85 g) was then filled as a chain transfer agent, followed by the addition of [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] -A methylcyclohexane solution (1.68 g) containing the activated transition metal compound (9.0 μmol-Hf) of Preparation Example 1 was poured into the reactor (9.0 μmol). The valve of the ethylene tank was opened to maintain the pressure in the reactor at 25 bar, and polymerization was carried out for 40 minutes. The temperature was adjusted within the range of 90 to 120° C., and the remaining ethylene gas was discharged.
[0205] When the temperature reached 90°C, Me3SiCH2Li·(PMDETA) solution prepared by mixing Me3SiCH2Li (244.8 mg, 2.6 mmol) and PMDETA (495.1 mg, 2.86 mmol) in methylcyclohexane (3.85 g) was added. The temperature was maintained at 90°C for 30 minutes with stirring, and then styrene (88.0 g) was added. The temperature was adjusted to the range of 90-100°C using a heating jacket.
[0206] of the fraction 1 H NMR analysis confirmed the complete conversion of styrene. After the complete conversion of styrene, 2-ethylhexanoic acid and ethanol were injected successively. The obtained polymer chunks (300 g) were dried in a vacuum oven at 80 °C overnight.
[0207] Example 2 A polyolefin-polystyrene multiblock copolymer was prepared in the same manner as in Example 1, except that the amounts of the organic zinc compound and styrene used were changed as shown in Table 1 below.
[0208] Comparative Manufacturing Example 1 The commercially available SEBS used was G1651 manufactured by Kraton.
[0209] Comparative Manufacturing Example 2 The transition metal compound was a compound represented by the following chemical formula, and was produced by the following method.
[0210] [ka]
[0211] A solution of trimethylaluminum (14.4 mg, 200 μmol-Al) dissolved in methylcyclohexane (17 g) was injected into the high-pressure reactor. The catalyst poison in the high-pressure reactor was purified at 100° C. for 1 hour, and the solution was removed using a cannula.
[0212] The organozinc compound (49.1 mg, 150 μmol) was dissolved in methylcyclohexane (40 g) and added to a high-pressure reactor, and the temperature was raised to 80° C. 18 H 37 )N(Me)H + [B(C6F5)4] - A solution of trioctylaluminum (4.0μmol) stirred in benzene for 2 hours was diluted with a solution (1.0g) of trioctylaluminum (50μmol, 18.3mg) dissolved in methylcyclohexane (15g). Immediately after injecting the catalyst solution into the high-pressure reactor, ethylene-propylene mixed gas was injected at a pressure of 20bar (propylene 10bar). The temperature was adjusted in the range of 95~115℃. The pressure gradually decreased due to consumption of the monomer, and the polymerization process was carried out at 45℃ for 60 minutes, after which the remaining gas was discharged.
[0213] Me3SiCH2Li (150μmol, 14.1mg) and PMDETA (150μmol, 26mg) were mixed with methylcyclohexane (1.0g) and injected into the reactor and stirred for 30 minutes. The stirring temperature was maintained at 90℃ to 100℃. Styrene (7.8g) was injected into the high pressure reactor and reacted for 5 hours at 90℃ to 100℃ to convert all the styrene monomer. After the complete conversion of the styrene monomer, acetic acid and ethanol were injected continuously. After obtaining the polymer, it was dried overnight in a vacuum oven at 180℃.
[0214] [Table 1]
[0215] Experimental Example 1 The properties of the polyolefin-polystyrene multiblock copolymers of the above-mentioned Preparation Examples 1 and 2 and Comparative Preparation Examples 1 and 2 were measured according to the following conditions and methods. The results are shown in Table 2.
[0216] (1) Storage modulus (E'), loss modulus (E") and tan δ values Using a DMA (Dynamic Mechanical Analysis) instrument, measurements were performed at a frequency of 1 Hz, strain of 0.1%, and temperature was increased from -90°C to 100°C at a rate of 5°C per minute.
[0217] (2) tan δ peak height This graph shows the change in loss tangent (tan δ) (y-axis) as a function of temperature (x-axis) obtained by dynamic mechanical analysis (DMA). The value of y was measured when the value of tan δ was maximum in the temperature range of -80 to 40°C.
[0218] (3) Half-width of tan δ peak The temperatures at half the height of the tan δ peak were designated as T1 and T2, respectively, and the width between T1 and T2 (T2-T1) was calculated.
[0219] [Table 2]
[0220] Experimental Example 2 (1) Weight average molecular weight (Mw, g / mol) and molecular weight distribution (polydispersity index, PDI) The weight average molecular weight (Mw, g / mol) and number average molecular weight (Mn, g / mol) were measured by gel permeation chromatography (GPC), and the weight average molecular weight was divided by the number average molecular weight to calculate the molecular weight distribution (polydispersity index, PDI).
[0221] -Column: PL Olexis -Solvent: TCB (trichlorobenzene) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160°C -Detector: Agilent High Temperature RI detector -Standard: Polystyrene - Using the Mark-Houwink formula, (K = 40.8 × 10 -5 , α=0.7057), molecular weight calculation using Universal Calibration
[0222] (2) Impact strength 90% by weight of a polypropylene homopolymerization agent and 10% by weight of the copolymer of the above-mentioned Example or Comparative Example were mixed in a twin-screw extruder and prepared into test pieces.
[0223] The impact strength (Notched Izod, J / m) was measured at temperatures of -30°C and 25°C, respectively, according to the standard measurement ASTM D256.
[0224] [Table 3]
[0225] Example 1 - Preparation of Thermoplastic Resin Composition 50 parts by weight of the polyolefin-polystyrene multiblock copolymer prepared in Example 1 was mixed with 50 parts by weight of a highly crystalline impact copolymer polypropylene (CB5230, manufactured by Daehan Petrochemicals) having a melt index (230°C, 2.16 kg) of 30 g / 10 min, and solution blended in xylene using a reactor to prepare a thermoplastic resin composition compound. At this time, the temperature was 200°C to 230°C, the impeller rotation speed was 400 rpm, and the blending time was 4 hours. After blending was completed, the compound was collected and dried overnight in a vacuum oven at 100°C.
[0226] Example 2 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the content of the polyolefin-polystyrene multiblock copolymer prepared in Example 1 and the content of the high crystalline impact copolymer polypropylene were changed to 80 parts by weight and 20 parts by weight, respectively.
[0227] Example 3 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene multiblock copolymer prepared in Example 2 was used instead of the polyolefin-polystyrene multiblock copolymer prepared in Example 1.
[0228] Example 4 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene multiblock copolymer prepared in Example 2 was used instead of the polyolefin-polystyrene multiblock copolymer prepared in Example 1.
[0229] Comparative Example 1 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene multiblock copolymer of Comparative Preparation Example 1 was used instead of the polyolefin-polystyrene multiblock copolymer prepared in Preparation Example 1.
[0230] Comparative Example 2 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene multiblock copolymer of Comparative Preparation Example 1 was used instead of the polyolefin-polystyrene multiblock copolymer of Preparation Example 1.
[0231] Comparative Example 3 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 1, except that the polyolefin-polystyrene multiblock copolymer of Comparative Preparation Example 2 was used instead of the polyolefin-polystyrene multiblock copolymer prepared in Preparation Example 1.
[0232] Comparative Example 4 - Preparation of Thermoplastic Resin Composition A thermoplastic resin composition compound was prepared in the same manner as in Example 2, except that the polyolefin-polystyrene multiblock copolymer of Comparative Preparation Example 2 was used instead of the polyolefin-polystyrene multiblock copolymer prepared in Preparation Example 1.
[0233] Experimental Example 3 The physical properties of the thermoplastic resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4 were measured according to the following conditions and methods. The results are shown in Table 4.
[0234] (1) Determination of ethylene, alpha-olefin and styrene content The copolymers of Example 1 and Comparative Example 1 were measured by NMR. A Bruker 600MHz AVANCE III HD NMR instrument was used. 1H NMR was measured under the conditions of ns=16, d1=3S, solvent=TCE-D2, 373K, and the TCE-d2 solvent peak was corrected to 6.0 ppm, and the content was calculated after confirming the CH3 of 1-propylene at 1 ppm and the CH3-related peak (triplet) of the butyl branch due to 1-hexene at around 0.96 ppm. The styrene content was calculated from the aromatic peak at around 6.5 to 7.5 ppm.
[0235] (2) Measurement of hardness (shore A) The hardness was measured according to ASTM D2240 using a TECLOCK GC610 STAND for Durometer and a Mitutoyo Shore hardness tester Type A.
[0236] (3) Compression set Using the thermoplastic resin compositions of Examples 1 and 2 and Comparative Examples 1 and 2, cylindrical test pieces with a thickness of 12.5±0.5 mm and a diameter of 29±0.5 mm were measured according to ASTM D-395. The test pieces were placed between two parallel metal plates, a spacer with a thickness of 9.5±0.02 mm was sandwiched between them, and the test pieces were compressed at room temperature (20±0.5°C). After 22 hours, the test pieces were removed from the compression device and left at room temperature (20±5°C) for 30 minutes, and the thickness was measured. Three test pieces were used in the same test, and the compression set was calculated according to the following formula 1.
[0237] [Formula 1] Compression set (%) = [(t0-t f ) / (t0-t s )] x 100
[0238] t0 is the initial thickness of the specimen, t f is the thickness of the test piece after cooling after heat treatment, t s is the thickness of the spacer.
[0239] (4) Melt flow rate (MFR) According to ASTM-D 1238, measurements were performed under conditions of 230°C and a load of 2.16 kg and 230°C and a load of 5 kg.
[0240] [Table 4]
[0241] As can be seen from Table 4, when comparing Examples 1 and 3 with Comparative Examples 1 and 3, and Examples 2 and 4 with Comparative Examples 2 and 4, respectively, which have the same multiblock copolymer content, the thermoplastic resin compositions of Examples 1 to 4 containing the polyolefin-polystyrene multiblock copolymers of Preparation Examples 1 and 2, respectively, exhibit significantly higher MFR values and lower compression set values than the thermoplastic resin compositions of Comparative Preparation Examples 1 and 2, respectively, which contain the polyolefin-polystyrene multiblock copolymers of Comparative Preparation Examples 1 and 2, respectively, and were found to exhibit excellent fluidity and excellent recovery force.
[0242] In addition, it was confirmed that the thermoplastic resin compositions of Examples 1 to 4 still maintained high hardness values, although they exhibited slightly lower hardness than the thermoplastic resin compositions of Comparative Examples 1 to 4. This confirmed that the thermoplastic resin compositions of Examples 1 to 4 maintained high hardness and exhibited high flowability and high restoring force.
Claims
1. (1) polypropylene, and (2) A method for producing a thermoplastic resin composition containing a polyolefin-polystyrene multiblock copolymer, which satisfies the following conditions (a) and (b) in a graph showing the change in loss tangent (tan δ) (y-axis) depending on temperature (x-axis) obtained by dynamic mechanical analysis (DMA), in a temperature range of −80 to 40° C.: The polyolefin-polystyrene multiblock copolymer is (S1) The following chemical formula 1: 【Chemistry 1】 [In the above Chemical Formula 1, R 1 ~R 11 are each independently hydrogen; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an arylalkoxy group having 7 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylalkyl group having 7 to 20 carbon atoms, The R 1 ~R 11 two or more adjacent rings among X 1 and X 2 are each independently hydrogen; a halogen; a hydroxy group; an amino group; a thio group; a silyl group; a cyano group; a nitro group; an alkyl group having 1 to 20 carbon atoms; an alkenyl group having 2 to 20 carbon atoms; an alkynyl group having 2 to 20 carbon atoms; a cycloalkyl group having 3 to 20 carbon atoms; an aryl group having 6 to 20 carbon atoms; an alkylaryl group having 7 to 20 carbon atoms; an arylalkyl group having 7 to 20 carbon atoms; a heteroaryl group having 5 to 20 carbon atoms; an alkoxy group having 1 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; an alkylamino group having 1 to 20 carbon atoms; an arylamino group having 6 to 20 carbon atoms; an alkylthio group having 1 to 20 carbon atoms; an arylthio group having 6 to 20 carbon atoms; an alkylsilyl group having 1 to 20 carbon atoms; or an arylsilyl group having 6 to 20 carbon atoms. In the presence of a catalyst composition containing a transition metal compound represented by the following chemical formula 4: 【Chemistry 2】 [In the above Chemical Formula 4, A is an alkylene having 1 to 20 carbon atoms; an arylene having 6 to 20 carbon atoms; or an arylene having 6 to 20 carbon atoms substituted with a halogen, an alkyl having 1 to 12 carbon atoms, a cycloalkyl having 3 to 12 carbon atoms, an alkoxy having 1 to 8 carbon atoms, or an aryl having 6 to 12 carbon atoms; B is an aryl having 6 to 12 carbon atoms substituted with an alkenyl having 2 to 12 carbon atoms. polymerizing an olefin monomer to form a polyolefin block using an organozinc compound represented by the formula: (S2) anionically polymerizing the polyolefin block and a styrene-based monomer in the presence of an alkyllithium compound containing a silicon atom and a triamine compound to form a polystyrene block; The polyolefin-polystyrene-based multiblock copolymer is a polystyrene-poly(ethylene-co-1-hexene)-polystyrene block copolymer having a weight average molecular weight of 40,000 to 300,000 g / mol, a molecular weight distribution of 1.0 to 3.0, and containing 10% by weight to 30% by weight of a polystyrene-based block. (a) a tan δ peak height of 0.45 to 0.60; and (b) The half width of the tan δ peak is 22.5 to 30.0°C.
2. The method for producing a thermoplastic resin composition according to claim 1, wherein under the condition (a), the tan δ peak is shown as one peak in the range of -50 to -30 ° C.
3. The method for producing a thermoplastic resin composition according to claim 1, wherein the half width of the tan δ peak under the condition (b) is 23.0 to 29.0 ° C.
4. The method for producing a thermoplastic resin composition according to claim 1, wherein the polyolefin-polystyrene multiblock copolymer further satisfies the following conditions (c) and (d): (c) at −10 to −30° C., the value of tan δ is 0.10 to 0.30; and (d) At 15 to 30° C., the value of tan δ is 0.05 to 0.
50.
5. The polyolefin-polystyrene multiblock copolymer has a storage modulus E' of 1 to 200 MPa and a loss modulus E" of 1 to 100 MPa at -10 to -30°C.
6. The polyolefin-polystyrene multiblock copolymer has a storage modulus E' of 0.1 to 50 MPa and a loss modulus E" of 0.01 to 5 MPa at 15 to 30°C.
7. 2. The method for producing a thermoplastic resin composition according to claim 1, wherein the polyolefin-polystyrene multiblock copolymer is produced without hydrogenating double bonds in the copolymer main chain.
8. The method for producing a thermoplastic resin composition according to claim 1, wherein the (1) polypropylene and the polyolefin-polystyrene multiblock copolymer have a weight ratio of 10:90 to 90:
10.
9. The method for producing a thermoplastic resin composition according to claim 1, wherein the thermoplastic resin composition satisfies the following physical properties (A) to (D): (A) Shore A hardness of 1 to 90, (B) a compression set of 0 to 80%; (C) a melt flow rate (MFR, 230°C, 2.16 kg) of 0.1 to 300 g / 10 min; (D) Melt flow rate (MFR, 230°C, 5 kg) is 0.1 to 500 g / 10 min.
Citation Information
Patent Citations
Thermoplastic elastomer resin composition and its production
JP1995330982A
Thermoplastic elastomer composition for boot and boot using the same
JP2002317096A
Thermoplastic polymer composition
JP2005068222A
Organozinc compound including polyolefin-polystyrene block copolymers and method for manufacturing thereof
KR101657925B1
Thermoplastic elastomer composition, plug, and container
WO2018139122A1